Pengaturan Pendayagunaan Sumber Daya Air dalam Undang-Undang Cipta Kerja dan Korelasinya dengan Pasal 33 UUD 1945 - Dimas Putra Pradhyksa (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2021)
Currently, the regulation regarding Water Resources is regulated in Law Number 17 of 2019 concerning Water Resources (“SDA Law”), and several provisions have been amended by Law Number 11 of 2021 concerning Job Creation (“Job Creation Law”). The existence of water resources, which is the constitutional right of every Indonesian citizen, is fundamental. Water should be the right of every layer of Indonesian citizens because the 1945 Constitution guarantees constitutional rights. Therefore, water must be controlled by the State and used as much as possible for the prosperity of the people. Based on Article 33 paragraph (2) and paragraph (3), Utilization of Water Resources can contextualize the paradigm of control over water resources between the Natural Resources Law, the Job Creation Law and its derivative regulations must prioritize the management of water resources with a state responsibility approach (State control) that prioritizes the interests of the State. Social needs (living needs of the people) and community involvement in planning for exploitation, protection, and financing of the benefits of irrigation have not yet detailed regulations regarding the use of water for the benefit of other industries.